Association between mitochondrial DNA content and baseline serum levels of HBsAg in chronic hepatitis B infection. Issue 11 (27th July 2017) - Chen, Tianbin; Xun, Zhen; Lin, Jinpiao; Fu, Ya; Wu, Wennan; Fu, Xiaochun; Hu, Yuhai; Zeng, Yongbin; Ou, Qishui
Abstract : Recent studies have demonstrated a potential link between mitochondrial DNA (mtDNA) content and cirrhosis or hepatocellular carcinoma (HCC). However, there are few studies evaluating mtDNA content as a noninvasive marker of chronic hepatitis B infection (CHB). In this study, we conducted a case‐control study to determine mtDNA content in peripheral blood leukocyte (PBL) samples from 76 CHB cases naïve to antivirus therapy and 96 healthy controls, and then evaluated the association between mtDNA content and baseline serum concentration of HBV markers. Consequently, CHB cases had significantly higher mtDNA content than healthy controls (1052.85 vs 618.98, P  < 0.001). Pearson's correlation analysis revealed that mtDNA content was negatively correlated with the baseline levels of hepatitis B surface antigen (HBsAg) ( r  = −0.291, P  = 0.011) in CHB patients. In a trend analysis, a statistically significant association was detected between lower mtDNA content and increasing levels of HBsAg ( P  = 0.015). In conclusion, our study provides the first epidemiological evidence that mtDNA content of CHB cases naive to antivirus therapy is significantly higher than healthy controls and the levels of mtDNA content is negatively associated with HBsAg. mtDNA content may serve as a potential noninvasive biomarker of CHB which may need more researches to validate. Abstract : CHB cases naïve to antivirus therapy have higher mtDNA content than healthy controls. mtDNA content is negatively correlated with the baseline levels of HBsAg in CHB. mtDNA content is a potential noninvasive biomarker of CHB.